FEV1 recovery following methacholine challenge in asthma: Variability and comparison of methods. (February 2020) - Singh, Dave; Khan, Naimat; Dean, James; Fowler, Andrew; Gupta, Abhya; Endriss, Verena; Iacono, Philippe; Disse, Bernd
Abstract: Background: Methacholine challenges have been used in clinical trials to assess therapeutic effects and potential adverse reactions of interventions on pulmonary function in a sensitive population, such as in subjects with asthma. Here, we evaluate the variability of the methacholine challenge recovery model, and compare the results obtained for both incremental and bolus challenge methods. Methods: The extent, time course and variability of change in forced expiratory volume in 1 s (FEV1 ) following repeated methacholine challenges in subjects with mild asthma were investigated in an open-label, four-period, fixed-sequence, two-method, replicate crossover study. At Visits 1 and 2, subjects underwent an incremental challenge using doubling doses of methacholine until a ≥20% decrease in FEV1 was observed; at Visits 3 and 4, subjects underwent a bolus challenge, inhaling a single dose of methacholine calculated from the cumulative dose established during Visit 1. Results: A total of 19 subjects were included in the study. Both the mean FEV1 area under the curve (FEV1 AUC0–tz ) and mean maximum reductions in FEV1 (absolute and relative) 120 min post-challenge values were higher for the incremental challenges than the bolus challenges, with no reported difference between repetitions of the same methodology. FEV1 AUC0–tz decrease 120 min post challenge demonstrated an intra-subject coefficient of variation (CV) of 47.2% (incremental) and 78.3% (bolus), suggesting considerable between-visit variability. The mean absolute, and similarly relative, maximum reductions in FEV1 compared with post-diluent baseline values demonstrated lower intra-subject variability (incremental 21.16%, bolus 40.67%) than the FEV1 AUC0–tz -based endpoint. There was a trend towards faster recovery following the bolus challenge than with the incremental challenge. The provocative dose of methacholine inducing a ≥20% decrease in FEV1 resulted in a between-group mean difference of 27.20% in the incremental challenge periods, with a high intra-subject CV of 80.64%, demonstrating considerable variability. Conclusion: Maximum reduction in FEV1 had the lowest variability. There was little difference between repetitions of the same methodology, as indicated by overlapping confidence intervals. There was a trend towards faster recovery following bolus challenge than with the incremental challenge. The results of this trial could be of value when designing future clinical trials using the methacholine challenge methodology. Abstract : Breathing in a chemical called methacholine (an approach known as methacholine challenge) has a similar effect on your airways to asthma, making them narrow. The methacholine challenge can be used to diagnose asthma. This study looked at two different methods for methacholine challenge. In one, people with asthma breathed in lots of small, increasing doses of methacholine until their airways had narrowed by a specific amount. In the other method, they breathed in only one larger dose, which was calculated from the total dose inhaled in the first approach. Scientists might use the results from this study to help design future trials that assess the ability of a novel therapy to protect against airway narrowing.